Complex regional pain syndrome and functional neurological disorders – time for reconciliation. Issue 5 (24th October 2018) - Popkirov, Stoyan; Hoeritzauer, Ingrid; Colvin, Lesley; Carson, Alan J; Stone, Jon
Abstract : There have been many articles highlighting differences and similarities between complex regional pain syndrome (CRPS) and functional neurological disorders (FND) but until now the discussions have often been adversarial with an erroneous focus on malingering and a view of FND as 'all in the mind'. However, understanding of the nature, frequency and treatment of FND has changed dramatically in the last 10–15 years. FND is no longer assumed to be only the result of 'conversion' of psychological conflict but is understood as a complex interplay between physiological stimulus, expectation, learning and attention mediated through a Bayesian framework, with biopsychosocial predisposing, triggering and perpetuating inputs. Building on this new 'whole brain' perspective of FND, we reframe the debate about the 'psychological versus physical' basis of CRPS. We recognise how CRPS research may inform mechanistic understanding of FND and conversely, how advances in FND, especially treatment, have implications for improving understanding and management of CRPS.